Potential of Indigenous Bacteria from Batik Wastewater as Cu Bioremediation Agent - Widiyanti, Devi; Khusnuryani, Arifah (Proceeding International Conference on Science and Engineering, 2021)
Abstract -Copper (Cu) is a heavy metal which can cause environmental problems in excessive amount. The presence of indigenous bacteria in a Cu-contaminated-environment can be used to reduce Cu levels in the environment. This study aims to determine the potential of bacteria isolated from batik wastewater as Cu bioremediation agent and to characterize those bacteria. Isolation of bacteria was carried out using the enrichment culture media consist of NB + 100 ppm CuSO4. The copper resistance test was carried out by growing bacterial isolates in NA media containing CuSO4 with concentrations of 200, 300, 400, 500, 600 and 700 ppm. The copper reduction test was determined by atomic absorption spectrophotometer. Bacterial identification was conducted by biochemistry characterization. The results showed that 10 bacterial isolates were able to grow on NA media containing 100 ppm CuSO4. Four bacterial isolates (namely ?3, ?5, ?8, and ?9) showed the highest resistance to CuSO4 (700 ppm). Bacterial isolates ?3, ?5, and ?9 were able to reduce Cu by up to 75,03%; 76,73%; and 76,34%. The three bacterial isolates showed similar characteristics to members of the Genus Xanthomonas. Isolate ?8 was able to reduce Cu up to 77,05% and was identified as member of the Genus Pseudomonas.